Numerical analysis of helicopter’s blade pitch link loads - Madeira, A.; Roucoules, L.; Malburet, F.; Serr, C.; Kelaidis, M. (My University, 2020)
The industrial process for the design of main rotor blades is more and more challenging. Taking into account the loads aspect in the blade design process became necessary to ensure a blade design that can be relevant with a high-speed usage. This paper presents the last results of recent studies about pitch link loads. Within the framework of the CHAllenge AeRothermoMEchanique project (CHARME) an important study has been made in order to understand and to improve the control loads prediction capability. The first part of this work was to identify the correct model to be used. A large study was done in order to understand different model’s effects, validity domain and relevance. The main goal of this part was to identify the most relevant aerodynamic modeling base to be used for the next step. All the models used are included in our global aeromechanic code. The second part of the work was to use this modeling base to identify the blade’s pitch link load of a state-ofthe-art main rotor blade during a high-speed forward flight.